New design concept of a downhill mountain bike frame made of a natural composite material - Collotta, M.; Solazzi, L.; Pandini, S.; Tomasoni, G. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
In this work, the design of a new downhill mountain bike frame, made with an innovative natural composite, is presented. The study is based on an early finite element analysis of the characteristics and performance of a standard frame made of aluminum, allowing to define the loading conditions and to provide a design optimization of the frame in different race situations. The model was later implemented with the properties of a natural reinforced composite. The results obtained show that the new composite allows a weight reduction with a stiffness and a safety coefficient comparable to the standard aluminum frame.